2020
DOI: 10.1088/1755-1315/421/2/022063
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biological drugs on phytosanitary condition of seeds of spring barley

Abstract: An important role is played to improve the stability of grain production for the modern protection of plants in the Republic of Mari El. A large number of areas allocated for grain crops are characterized as not favorable phytosanitary conditions, where the shortage of crops can reach 25 percent or more in the republic’s farms. The phytosanitary condition of cereal lands is permissible on the basis of the development of protective measures, optimization and intensification of factors that affect the size of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A detailed analysis of the impact of new nutrient complexes in combination with organic and organo-mineral nutrition on the yield of spring barley showed that their use and increased droughts and dry winds, especially in the southern regions of our country. This is not only a problem of Ukraine, but also a global problem, as evidenced by studies (Cammarano et al, 2020;Carter et al, 2019;Sallam et al, 2019;Solonechnyi et al, 2015;Toymetov and Maryina-Chermnykh, 2020;Yurkevich et al, 2011) . The increased droughts in the south of Ukraine leads to the fact that intensive varieties of spring barley cannot use their full potential, resulting in a significant yield reduction (Vinyukov et al, 2016).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A detailed analysis of the impact of new nutrient complexes in combination with organic and organo-mineral nutrition on the yield of spring barley showed that their use and increased droughts and dry winds, especially in the southern regions of our country. This is not only a problem of Ukraine, but also a global problem, as evidenced by studies (Cammarano et al, 2020;Carter et al, 2019;Sallam et al, 2019;Solonechnyi et al, 2015;Toymetov and Maryina-Chermnykh, 2020;Yurkevich et al, 2011) . The increased droughts in the south of Ukraine leads to the fact that intensive varieties of spring barley cannot use their full potential, resulting in a significant yield reduction (Vinyukov et al, 2016).…”
Section: Resultsmentioning
confidence: 96%
“…As for this agrotechnical method of fertilizer system using biopreparations and plant growth regulators, studies in Western and Eastern Europe show that the treatment of crops with a complex of plant growth regulators increases the productivity of these crops by 15-30% (Rassokhina et al, 2020;Toymetov and Maryina-Chermnykh, 2020). This is influenced by such factors as: reducing the incidence of plant root rot, increasing the leaf surface of barley plants resulting from increased photosynthetic activity, reduced negative effects of stress, increased drought resistance of plants, etc.…”
Section: Resultsmentioning
confidence: 99%